1992
DOI: 10.1073/pnas.89.24.12008
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus gp120 binding C'C" ridge of CD4 domain 1 is also involved in interaction with class II major histocompatibility complex molecules.

Abstract: Using site-directed mutagenesis informed by high-resolution CD4 structural data, we have investigated the role of residues of the C'C" ridge region of human CD4 on class H major histocompatibility complex (MHC) binding. This (17,18) results in diminished CD4+ T-cell development and impairment of B-cell functions. In mature T lymphocytes, CD4 crosslinking is known to provide a costimulatory signal during T-cell activation via the T-cell receptor (TCR) (19,20). The signaling functions of CD4 are believed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 46 publications
3
63
0
Order By: Relevance
“…COS-7 cells transfected with pcDNA3 vector alone served as negative controls, which showed no rosette formation. Other studies have demonstrated that the enumeration of rosetting as performed here correlates well with quantitative cell binding assays employing radiolabeled Raji cells (16).…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…COS-7 cells transfected with pcDNA3 vector alone served as negative controls, which showed no rosette formation. Other studies have demonstrated that the enumeration of rosetting as performed here correlates well with quantitative cell binding assays employing radiolabeled Raji cells (16).…”
Section: Methodssupporting
confidence: 63%
“…CD4-MHC class II binding studies, using a cell rosetting assay (5,16), were performed to test this hypothesis. Peptide IV inhibited rosette formation by as much as 50% in a concentrationdependent manner (Fig.…”
Section: Fig 4 Inhibitory Effect Of the Cyclic Heptapeptide IV (Cnsmentioning
confidence: 99%
“…Other studies have shown that the enumeration of rosetting as performed here correlates well with quantitative cell binding assays employing radiolabeled Raji cells (20).…”
Section: Animals Female Sjl͞j H2mentioning
confidence: 56%
“…The inhibition of stable CD4-MHC class II binding by the compounds selected from computer screening studies was assessed in a standard cell adhesion assay that has been shown by several laboratories to accurately reflect this functional interaction (8,16,20). Following a modified procedure of Moebius et al (20), 5 ϫ 10 4 COS-7 cells per well of a 6-well plate were transfected with T4-pcDNA3 (Invitrogen) by DOSPER liposomal transfection (Boehringer Mannheim) according to the supplier's protocol for the reagent.…”
Section: Animals Female Sjl͞j H2mentioning
confidence: 99%
“…Interaction with pMHCI is via the six antibody-like CDR loops, three from each subunit Ig domain (47,48). In contrast, CD4 interaction with pMHCII involves the D1-D2 module including residues outside of the CDR regions (13,49,50). Perhaps more importantly, the membrane proximal CD4 segment is not a flexible stalk but rather is composed of two Ig-like domains.…”
Section: Discussionmentioning
confidence: 99%